Comparative effects of genistein and bisphenol A on non-alcoholic fatty liver disease in laying hens. (1st November 2021) - Gao, Xiaona; Liu, Shuhui; Ding, Chenchen; Miao, Yufan; Gao, Zhangshan; Li, Mengcong; Fan, Wentao; Tang, Zhihui; Mhlambi, Nobuhle Hyacinth; Yan, Liping; Song, Suquan
Abstract: Bisphenol A (BPA) and genistein (GEN) are selective estrogen receptor modulators, which are involved in the occurrence and development of metabolic syndrome. However, their roles in non-alcoholic fatty liver disease (NAFLD) of laying hens have not been reported. Here, we investigated the effects of different concentrations of GEN and BPA on the NAFLD of laying hens. Results showed that GEN ameliorated the high-energy and low-protein diet (HELP)-induced NAFLD by improving pathological damage, hepatic steatosis, and insulin resistance and blocking the expression of NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome-related factors. By contrast, high dose of BPA could aggravate these changes with serious symptom of NAFLD and suppress the level of ERα in the liver considerably, while GEN could reverse this phenomenon in a dose-dependent manner. In general, our research shows that the protective effect of GEN on NAFLD aims to improve the metabolic disorders and inflammation closely connected to ERα, while BPA can inhibit the expression of ERα and exacerbate the symptom of NAFLD. In conclusion, we elucidate the opposing effects of GEN and BPA in NAFLD of laying hens, thus providing a potential mechanism related to ERα and inflammation. Graphical abstract: Image 1 Highlights: BPA exposure markedly increased lipid deposition and inflammation in the liver of laying hens. BPA exposure decreased expression of ERα, aggrieved NAFLD in laying hens. Genistein ameliorated the hepatic steatosis and inflammation in laying hens by activating ERα. The NLRP3 inflammasome is associated with NAFLD of laying hens.